Obligation to be Registered as Participant of National Health Insurance in Land Registration from Sale and Purchase from State Responsibilities Perspective - Cicilia Mirnasari Putri; Albertus Sentot Sudarwanto (Global Writing Academica Researching and Publishing, 2022)
The right to health is one of the human rights guaranteed by the 1945 Constitution of the Republic of Indonesia and is a state responsibility that must be fulfilled. One manifestation of the implementation of these rights is to organize the National Health Insurance program. However, current facts and data show that participants from the National Health Insurance have not reached 100%, so to achieve this the government issued Presidential Instruction Number 1 of 2022, one of which requires applicants to register for the transfer of land rights because the sale and purchase is an active participant in the Health Insurance program. National. The author considers the government's policy through the Presidential Instruction to be wrong based on theories related to state responsibility, laws related to buying and selling land in Indonesia, and the concept of state control over land in Indonesia. In the end, the author analyzes that this policy will actually be contradictory to other governments, namely all land in Indonesia must have a certificate for the realization of legal certainty over land throughout Indonesia.